Postlogging effects on suspended solids and turbidity-five years observation. - Yusop, Zulkifli; Suki, Anhar; Kasran, Baharuddin (1990)
Five years data for postlogging period were analyzed to evaluate the impact of two selective logging methods namely, "Unsupervised" and "Supervised" on Suspended Solids and Turbidity levels. With respect to turbidity, the streamwater quality of undisturbed forest generally exceeded the recommended limit for portable use. Suspended solids and turbidity levels were both increased by five and nine folds, respectively during the first year after unsupervised logging. However, the increases due to supervised logging were small and revert to background level in the second year. Suspended solids transports for undisturbed state ranged from 0.08 to 0.24 mt/ha/yr. The levels were elevated following unsupervised logging, by 20 folds in the first year and remained high, between four to five folds in the subsequent years. Nevertheless, for supervised logging the suspended solids loads were only two folds as high as the control's.